EVALUATION OF POTENTIAL BIOACTIVITIES OF SECONDARY METABOLITES EXTRACTED FROM THE ENTOMOPATHOGENIC FUNGI - S.KARTHICK RAJA NAMASIVAYAM,; R.S.ARVIND BHARANI,; M.BAVANI LATHA, (International Journal of Pharma and Bio Sciences, 2014)
Entomopathogenic fungi are a group of fungal organisms associated with insects and extensively used in various parts of the world as biopesticides against economic important insect pests. Various secondary metabolites produced by entomopathogenic fungi has a lot of potential biological activities such as antimicrobial and insecticidal activities. The present study is undertaken to evaluate the possible bioactive components in the ethyl acetate extract of entomopathogenic fungi Beauveria bassiana and Nomuraea rileyi and evaluation of potential biological activities such as anti microbial and insecticidal activities. Metabolites were extracted from culture free supernatant of the media after the extraction with ethyl acetate. Screening of possible components was carried out by GC-MS.GC-MS analysis of ethyl acetate extract of both the fungal organism was performed using a Perkin-Elmer GC Clarus 500 system comprising an AOC-20i auto-sampler and a gas chromatograph interfaced to a mass spectrometer (GC-MS) Metabolites with different concentrations was used to study anti bacterial activity against human pathogenic bacteria Escherichia coli, Salmonella typhi and Enterococci species adopting dynamic growth curve inhibition assay and cytotoxicity against Spodoptera frugiperda-21 cell line (-21) adapting 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Both the fungal metabolites were found to cause distinct anti bacterial and cytotoxicity as dose dependent manner. The present study would suggest the possible utilisation of entomopathogenic fungal metabolites as an effective agent for controlling the economic important Lepidopteron insect pests.